To strengthen self-confidence as a step in improving prehospital youth laymen basic life support - Abelsson, Anna (BMC Emerg Med, 2020)
BACKGROUND: A rapid emergency care intervention can prevent the cardiac arrest from resulting in death. In order for Cardio Pulmonary Resuscitation (CPR) to have any real significance for the survival of the patient, it requires an educational effort educating the large masses of people of whom the youth is an important part. The aim of this study was to investigate the effect of a two-hour education intervention for youth regarding their self-confidence in performing Adult Basic Life Support (BLS). METHODS: A quantitative approach where data consist of a pre- and post-rating of seven statements by 50 participants during an intervention by means of BLS theoretical and practical education. RESULTS: The two-hour training resulted in a significant improvement in the participants’ self-confidence in identifying a cardiac arrest (pre 51, post 90), to perform compressions (pre 65, post 91) and ventilations (pre 64, post 86) and use a defibrillator (pre 61, post 81). In addition, to have the self-confidence to be able to perform, and to actually perform, first aid to a person suffering from a traumatic event was significantly improved (pre 54, post 89). CONCLUSION: By providing youth with short education sessions in CPR, their self-confidence can be improved. This can lead to an increased will and ability to identify a cardiac arrest and to begin compressions and ventilations. This also includes having the confidence using a defibrillator. Short education sessions in first aid can also lead to increased self-confidence, resulting in young people considering themselves able to perform first aid to a person suffering from a traumatic event. This, in turn, results in young people perceiveing themselves as willing to commence an intervention during a traumatic event. In summary, when the youth believe in their own knowledge, they will dare to intervene.